ANALISIS PANJANG GANDENGAN TERHADAP DITRIBUSI DAYA OPTIK - Yussa Ananda (Universitas Harapan Medan, 2021)
Optical fiber is a transmission medium that is widely used for local networks. In optical fiber transmission media there are various kinds of losses, including: Coupling losses, splicing losses, bending losses and attenuation losses in the connector. In this final project, the calculation of optical fiber losses is carried out. As for the observed length of the optical power coupling with the output obtained by the Directional Coupler. Fabrication and characterization of Directional coupler on fiber material with stripping lengths of 34mm and 28mm using the BF5RD1-N approach to the Fused Biconical Tapered (FBT) method which produces different characterization results and meets fabrication standards. The results of the directional coupler characterization using Microsoft Excel and BF5RD1-N obtained parameters CR (Coupling Ratio), Le (ExcessLoss), Lins (Insertion Loss) and D (Directivity). In the directional coupler, using each formula the value of CR=0.34; Le= -4dB; Lins= -11,21